2016
DOI: 10.1111/jcmm.12851
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between vasculogenic mimicry and epithelial‐mesenchymal transitions

Abstract: Vasculogenic mimicry ( VM ) is a vascular‐like structure which can mimic the embryonic vascular network pattern to nourish the tumour tissue. As a unique perfusion way, VM is correlated with tumour progression, invasion, metastasis and lower 5‐year survival rate. Notably, epithelial‐mesenchymal transition ( EMT ) regulators and EMT ‐related transcription factors are highly up‐regulated in VM ‐form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
97
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(101 citation statements)
references
References 83 publications
3
97
0
1
Order By: Relevance
“…Recent studies have shown that EMT, in which the cell‐cell junction is lost and cells lose the epithelial phenotype and acquire mesenchymal features, is a critical step in the process of cancer metastasis . Additionally, EMT plays a crucial role in VM formation . In our study, we tested whether EMT participates in the inhibition of VM formation by TP53INP1.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies have shown that EMT, in which the cell‐cell junction is lost and cells lose the epithelial phenotype and acquire mesenchymal features, is a critical step in the process of cancer metastasis . Additionally, EMT plays a crucial role in VM formation . In our study, we tested whether EMT participates in the inhibition of VM formation by TP53INP1.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, many studies have proposed that EMT is vital for VM formation and tumor progression (9). Some regulatory factors, such as Twist, Runx2 and ZEB2, play important roles in VM formation by promoting EMT (6,16,17).…”
Section: Discussionmentioning
confidence: 99%
“…EMT is regulated by many transcription factors, including the traditional factor ZEB1. The role of EMT in the development of VM has recently attracted attention (9,15,16). Liu et al (8) confirmed that ZEB1 can promote VM formation by inducing EMT in colorectal cancer.…”
Section: Vasculogenic Mimicry In Bladder Cancer and Its Association Wmentioning
confidence: 99%
See 1 more Smart Citation
“…Further evidences have found that EMT regulators and EMT-related transcription factors are highly upregulated in VM-forming tumor cells 27. Many studies have demonstrated that adhesion molecules and other factors modulating EMT process can regulate VM formation, such as Twist, ZEB1, Snail, and Slug/Snail2 14. In this study, we performed an IHC stain of E-cadherin, a well-established indicator of EMT, and discovered that VM was associated with EMT.…”
Section: Discussionmentioning
confidence: 79%